Pelatihan Microsoft Office bagi Perangkat Desa Adipuro Kaliangkrik untuk Meningkatkan Pelayanan pada Masyarakat - Tri Yusnanto (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: Autonomy has given rise to extraordinary enthusiasm at the village level, it does not mean that there are no serious problems originating from internal villages. This is constrained because the village document processing field in Adipuro is still done manually and in computer skills in the range of 40%. Therefore, training is needed to improve the skills of village officials in Adipuro, especially Microsoft Office. With the hope that the device acquires knowledge in supporting its work and activities, to facilitate its work in managing village administration, and can convey its knowledge to the community in its environment. Methodology: The method used is the lecture method, practicum and mentoring regarding the use of Microsoft Office, it is hoped that after conducting the training, village officials can operate computers and use Microsoft Office well. Result: From the results of Community Service that has been carried out by the entire team, both lecturers and students with the title Microsoft Office Training for Adipuro Kaliangkrik Village Devices to Improve Community Services, it went smoothly and successfully with a range of 80%. Conclusion: After receiving this training they are able to use Ms Offices, especially Microsoft Word in facilitating services to the community such as making recommendation letters for moving domicile, making death certificates and so on.